Assessing school‐aged children's inference‐making: the effect of story test format in listening comprehension. Issue 1 (14th June 2016) - Freed, Jenny; Cain, Kate
Abstract: Background: Comprehension is critical for classroom learning and educational success. Inferences are integral to good comprehension: successful comprehension requires the listener to generate local coherence inferences, which involve integrating information between clauses, and global coherence inferences, which involve integrating textual information with background knowledge to infer motivations, themes, etc. A central priority for the diagnosis of comprehension difficulties and our understanding of why these difficulties arise is the development of valid assessment instruments. Aims: We explored typically developing children's ability to make local and global coherence inferences using a novel assessment of listening comprehension. The aims were to determine whether children were more likely to make the target inferences when these were asked during story presentation versus after presentation of the story, and whether there were any age differences between conditions. Methods & Procedures: Children in Years 3 ( n = 29) and 5 ( n = 31) listened to short stories presented either in a segmented format, in which questions to assess local and global coherence inferences were asked at specific points during story presentation, or in a whole format, when all the questions were asked after the story had been presented. Outcomes & Results: There was developmental progression between age groups for both types of inference question. Children also scored higher on the global coherence inference questions than the local coherence inference questions. There was a benefit of the segmented format for younger children, particularly for the local inference questions. Conclusions & Implications: The results suggest that children are more likely to make target inferences if prompted during presentation of the story, and that this format is particularly facilitative for younger children and for local coherence inferences. This has implications for the design of comprehension assessments as well as for supporting children with comprehension difficulties in the classroom.